Strategi Kepala Madrasah dalam Meningkatkan Mutu Pendidikan Melalui Supervisi Akademik di MAN Kota Singkawang - Legimin Legimin; Hifza Hifza; Asman Asman (Pusat Riset dan Inovasi Nasional, 2024)
The phenomenon that occurred in MAN sors in the implementation of academic supervision of the Principal in improving the quality of education in MAN Singkawang City. The research method used is a qualitative approach with data collection techniques through in-depth interviews with the Principal, Deputy Head of Curriculum, and teachers at MAN Singkawang City. The data obtained were analyzed using a descriptive approach, namely reduction, data display, and drawing conclusions. The results of the study show that 1) the implementation of academic supervision at MAN Singkawang City involves a series of activities, such as class visits, observations, personal conversations with teachers, and ongoing coaching. 2) Evaluation of supervision results resulted in follow-up in the form of coaching focused on developing teachers' pedagogical competencies. 3) However, several obstacles to the implementation of supervision were encountered, such as unexpected schedule changes, less than optimal teacher preparedness, and limited facilities. Nevertheless, the implemented solutions, such as schedule adjustments and the use of technology, successfully addressed these obstacles and increased the effectiveness of supervision in improving the quality of education in madrasas.